A prospective, multisite, international validation of the Complex Regional Pain Syndrome Severity Score. Issue 8 (August 2017) - Harden, R. Norman; Maihofner, Christian; Abousaad, Elias; Vatine, Jean-Jacques; Kirsling, Amy; Perez, Roberto S.G.M.; Kuroda, Maxine; Brunner, Florian; Stanton-Hicks, Michael; Marinus, Johan; van Hilten, Jacobus J.; Mackey, Sean; et al.
Abstract : Abstract: Clinical diagnosis of complex regional pain syndrome (CRPS) is a dichotomous (yes/no) categorization, a format necessary for clinical decision making. Such dichotomous diagnostic categories do not convey an individual's subtle gradations in the severity of the condition over time and have poor statistical power when used as an outcome measure in research. This prospective, international, multicenter study slightly modified and further evaluated the validity of the CRPS Severity Score (CSS), a continuous index of CRPS severity. Using a prospective design, medical evaluations were conducted in 156 patients with CRPS to compare changes over time in CSS scores between patients initiating a new treatment program and patients on stable treatment regimens. New vs stable categorizations were supported by greater changes in pain and function in the former. Results indicated that CSS values in the stable CRPS treatment group exhibited much less change over time relative to the new treatment group, with intraclass correlations nearly twice as large in the former. A calculated smallest real difference value revealed that a change in the CSS of ≥4.9 scale points would indicate real differences in CRPS symptomatology (with 95% confidence). Across groups, larger changes in CRPS features on the CSS over time were associated in the expected direction with greater changes in pain intensity, fatigue, social functioning, ability to engage in physical roles, and general well-being. The overall pattern of findings further supports the validity of the CSS as a measure of CRPS severity and suggests it may prove useful in clinical monitoring and outcomes research. Abstract : Supplemental Digital Content is Available in the Text.Our findings support the validity of the CRPS Severity Score (CSS) as a measure of severity of the clinical disease state, and suggest it may prove useful in clinical monitoring and outcomes research.